Long-term association of Tyrannus savana and Sturnella superciliaris density with land cover and climatic variables in agroecosystems of Argentina - Calamari, Noelia Cecilia; Cerezo, Alexis; Canavelli, Sonia Beatriz; Dardanelli, Sebastian; Gavier Pizarro, Gregorio Ignacio; Zaccagnini, Maria Elena (Aves Argentinas/Asociación Ornitológica del Plata, 2018)
Agricultural expansion and intensification resulted in important changes in the agricultural landscape of the Pampas region, Argentina. We used linear mixed models to analyze the relationship between environmental variables associated to land use/cover, productivity and climate and changes in densities of two bird species, the Fork-tailed Flycatcher (Tyrannus savana) and the White-browed Blackbird (Sturnella superciliaris). The study area in central Argentina was divided in three agroproductive sub-regions: (1) predominantly agricultural, (2) mixed agricultural- rangeland and (3) mixed agricultural-forested rangeland. Bird populations were sampled annually during 2003-2011 using point-transects along secondary roads (48 transects). Mean estimated density for Fork-tailed Flycatcher was 0.132 ind/ha, increased in the agricultural sub-region and was associated with decreasing forest cover and increasing fallow and weedy fields cover. Mean density of the White-browed Blackbird was 0.045 ind/ha, decreased in the agricultural-rangeland sub-region and increased in landscapes with more perennial pastures, fallow and weedy fields and annual pastures, avoiding sites with more forest cover. Productivity and climatic variables only showed a strong association with White-browed Blackbird density. Our results suggest that land use/cover, productivity and climatic factors are important variables when planning strategies to conserve bird population at a regional level in agroecosystems of Argentina.